Pola as Joyce's Negative Epiphany, 9.11.2011. James Joyce Centre, Dublin, Ireland - Gjurgjan, Ljiljana Ina (2011)
The lecture claims that Joyce's Dubliners foreshadow the modernist and even more postmodern unease in relation to the Cartesian notion of subject, truth, and narrative closure. Drawing upon Joyce's best known aesthetic concept epiphany the lecture argues that the narrative procedure in his early stories can be described as negative epiphany as they point to something that is concealed, missing and suppressed.